Educar para conservar: Educação ambiental na formação continuada de professores no município de Caaporã - PB - Cavalcanti, Júlia Nazário de Abreu (2013)
The Environmental Education (EE) is a topic of significant cultural value and necessary for the formation of citizenship, should be implemented in educational programs as recommended by the National Policy on EE. However, that issue is not present in the continuing education of teachers of public primary schools I and II of the municipality of Caaporã-PB. Local environmental issues are visible, and in this city there is a conservation-called Extractive Reserve Acaú-Goiana with Mangrove Ecosystem of extreme biological and socioeconomic importance to the local community. Based on this, this study aimed to investigate the conceptions of teachers about the prospect of EA implement this theme in the continuing education of teachers in public schools. In this context, the present study and characterized as a qualitative research, and as a source of research, a universe composed of 24 faculty employees and two managers of Municipal Elementary School Elementary and Middle School Adauto Viana and Municipal Elementary School Severina Helena, both schools surveyed during this study are considered significant number of references for students and teachers. Regarding data collection, this took place in three stages, the first stage was carried out using a questionnaire to identify the functional structure and pedagogical schools and structured pre-test applied to teachers. In the second stage, there were six teaching workshops during the months from March to May 2012. Finished up the research in June 2012 with the implementation of a post-test after the workshops, issues similar to the pre-test. The results were satisfactory, obtaining confirmation of the hypothesis under discussion, identified mainly contradictory conceptions of teachers about some of the themes discussed in workshops like the concept EE, Environment and Sustainability, when they emphasized the responses of the pre-test that EE is only related to ecology theme, the Environment only restricted to biotic and abiotic stresses and Sustainability would be the practice of some environmental management actions. From the results obtained, it has been proposed to implement EE in continuing education programs for teachers of the county, so that they have specific expertise in this subject, and to develop greater security pedagogical practices in the public schools of that city.